Jenis atap, suhu dan kelembaban dalam rumah - Fatimah Fatimah; Juanda Juanda; Imam Santoso (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2019)
Abstrack: Type of roof, temparature and humidity in the house. The roof is the largest element that receives sun exposure. The type of roof affects the amount of heat energy that can be absorbed of reflected. The temperature and humidity in the room.This study aims to determine the relationship between the type of roof with temperature and humidity in the house in the Badaun village. This research use cross sectional design with variation of roof type was leaf, asbestos and iron sheeting. The study population was 68 houses and was analyzed using Somers'd test.The results showed that the proportion of leaf roof, asbestos and iron sheeting were 36.8%, 10.3% and 52.9%, respectively. Average home room temperature using a leaf roof type of 29.6°C, 32°C asbestos roof and 32.1°C iron sheeting roof. The average humidity of the house that uses the leaf roof is 72.28%, asbestos 55.7% and iron sheeting 57.3%. The results of the analysis using the Somers'd test proved statistically there is a strong relationship between the type of roof of the house (leaves, asbestos and zinc) with the temperature and humidity in the house in Badaun Village, Tapin District. Every home that uses zinc and asbestos roof 27 times the risk (OR = 27) hotter than the house using a leaf roof. Efforts that can be done to cope with higher temperatures and humidity is in the effort to install the ceiling of the house and always open the doors and windows every morning.